2018
DOI: 10.1002/jlb.mr0618-233r
|View full text |Cite
|
Sign up to set email alerts
|

The role of myeloid-derived suppressor cells in chronic infectious diseases and the current methodology available for their study

Abstract: An effective pathogen has the ability to evade the immune response. The strategies used to achieve this may be based on the direct action of virulence factors or on the induction of host factors. Myeloid‐derived suppressor cells (MDSCs) are immune cells with an incredible ability to suppress the inflammatory response, which makes them excellent targets to be exploited by pathogenic bacteria, viruses, or parasites. In this review, we describe the origin and suppressive mechanisms of MDSCs, as well as their role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 147 publications
(356 reference statements)
0
25
0
Order By: Relevance
“…In addition to mature neutrophils, under pathogenic conditions such as chronic inflammatory disease and cancer, immature myeloid cells, known as myeloid-derived suppressor cells (MDSCs), are recruited from the bone marrow prior to terminal differentiation [85,108]. Granulocytic MDSCs (G-MDSCs) are thought to be immature neutrophils since they morphologically and phenotypically resemble neutrophils.…”
Section: Tumour-associated Neutrophilsmentioning
confidence: 99%
“…In addition to mature neutrophils, under pathogenic conditions such as chronic inflammatory disease and cancer, immature myeloid cells, known as myeloid-derived suppressor cells (MDSCs), are recruited from the bone marrow prior to terminal differentiation [85,108]. Granulocytic MDSCs (G-MDSCs) are thought to be immature neutrophils since they morphologically and phenotypically resemble neutrophils.…”
Section: Tumour-associated Neutrophilsmentioning
confidence: 99%
“…In response to bacterial infection, MDSC recruitment and activity are typically associated with resolution and/or chronicity (28). This has been described during pulmonary infections caused by Pseudomonas aeruginosa (28) and nonpulmonary infections with major pathogens such as Staphylococcus aureus, Salmonella enterica, and Porphyromonas gingivalis (10,13,14,(29)(30)(31)(32)(33)(34). In each of these cases, recruited MDSCs inhibit the innate and adaptive immune responses, causing chronic infection.…”
Section: Figmentioning
confidence: 99%
“…Finally, even though the transfer of non-IL-10-producing BM-MDSCs did not have an effect on bacterial clearance and lung inflammation, it had a positive impact on host survival by either delaying host mortality or improving host survival from 0% to 25%. It has been reported that BM-MDSCs can efficiently suppress T cell activation through the activity of arginase-1, iNOS, Cox2, vascular endothelial growth factor (VEGF), Ido1, and other factors (28). It is highly possible that these molecules also have an important role in the modulation of the inflammatory response during KP35 infection; however, more studies are needed to establish the real contribution and the mechanisms involved.…”
Section: Figmentioning
confidence: 99%
“…In addition to mature neutrophils, under pathogenic conditions such as chronic inflammatory disease and cancer, immature myeloid cells, known as myeloid-derived suppressor cells (MDSCs), are recruited from the bone marrow prior to terminal differentiation [68,90]. Granulocytic MDSCs (G-MDSCs) are thought to be immature neutrophils since they morphologically and phenotypically resemble neutrophils.…”
Section: Tumour Associated Neutrophilsmentioning
confidence: 99%